2018
DOI: 10.1002/mawe.201700154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of scratch depth on vacuum tightness of diffusion bonded parts

Abstract: The surface roughness or solitary grooves decides about success or failure of diffusion bonding and vacuum tightness of the parts to be welded. Since surfaces have to be mated at atomic level to enable diffusion of atoms across bonding planes, also single deep scratches must be avoided to achieve vacuum tightness. Up to now there are no criteria which grooves can be tolerated. In fact, personal experience of the operator is essential to evaluate the surface before diffusion bonding. In this paper different loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Differences may appear when material is removed out of the surface or burrs form at the rim. Investigations of depths of scratches were performed in [11]. It was found that a temporary increase of bearing pressure that activates creep of material helps to close scratches.…”
Section: Figure 12mentioning
confidence: 99%
“…Differences may appear when material is removed out of the surface or burrs form at the rim. Investigations of depths of scratches were performed in [11]. It was found that a temporary increase of bearing pressure that activates creep of material helps to close scratches.…”
Section: Figure 12mentioning
confidence: 99%
“…However, unfortunately, different roughness values were not investigated and compared. In [5], we investigated the depth of singular scratches on vacuum tightness and compared the impact of a constant contact pressure to a contact pressure superimposed by short peak loads. However, the influence of the absolute width of joining cross sections on the deformation behavior has not yet been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%
“…However, different roughness values were not investigated and compared. In [12], the authors investigated the depth of singular scratches on vacuum tightness and compared the impact of constant contact pressure to a contact pressure superimposed by short peak loads. However, the impact of the absolute width of joining cross-sections on the deformation behavior was not yet investigated systematically.…”
Section: Introductionmentioning
confidence: 99%